IDENTIFICATION OF GRAM-NEGATIVE BACTERIAL ISOLATES FROM PIG TONSILS BASED ON MORPHOLOGY AND BIOCHEMICAL TEST - Nataswara, Yan Agus Dharma; Suardana, I Wayan; Suartini, I Gusti Ayu Agung (Buletin Veteriner Udayana, 2025)
Gram-negative bacteria are microorganisms characterized by significant pathogenic potential and are implicated in a wide range of infections affecting both humans and animals. The tonsils, as lymphoid organs integral to the immune system, can act as niches for bacterial colonization due to their conducive microenvironment for microbial growth. This study aimed to identify Gram-negative bacterial species isolated from porcine tonsils through morphological characterization, oxidase testing, and biochemical profiling using the Methyl Red–Voges-Proskauer (MR-VP) tests, as well as to determine the proportional distribution of the identified bacterial taxa. A total of ten presumptive Gram-negative bacterial isolates, preserved in 30% glycerol, were examined at the Veterinary Public Health Laboratory, Faculty of Veterinary Medicine, Udayana University. The isolates underwent Gram staining, oxidase assay, and MR-VP biochemical testing. The results revealed that seven of the ten isolates (70%) were identified as Pseudomonas spp., while the remaining three isolates (30%) belonged to the family Enterobacteriaceae. All isolates tested positive for the MR test, whereas eight isolates were positive and two negative in the VP test. These findings suggest that porcine tonsils may serve as reservoirs for Gram-negative bacteria, particularly Pseudomonas spp. and members of the Enterobacteriaceae family, which may possess zoonotic potential and thus warrant further surveillance and risk assessment.